La réflexivité infirmière en formation, entre injonction et allant-de-soi - Catherine Aubouin; Gilles Monceau (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In France, a reengineering of nursing studies took place in 2009. This reform accompanies an overall evolution of the profession and has profoundly transformed the training system. From now on, the analysis of nursing activity in situations is considered the main source of learning. Students learn from, through and for professional situations. Two categories of trainers, those working in nursing training institutes on the one hand, and nurses in post responsible for tutoring placements on the other hand, contribute together to monitoring the student during his or her training course. They are in charge of accompanying the reflexive process by which the student must build his self-training in alternation between the training institute and the internship field.This article examines the way in which these trainers have experienced this evolution, during which the new paradigm of reflexivity and the redefinition of the notion of competence have shaken up their conception of the profession and their professional posture.The results show that the reflective training and the professionalization injunction, now expected in nursing training, has caused the posture of its trainers to evolve from a "traditional and transmissive" training position to a posture of pedagogical support. Practitioners who have become placement tutors are called upon to take on a pedagogical skill that was previously considered to be specific to trainers working in training institutes, while the latter have to rework their pedagogical conception in order to carry out a work of support for learning that moves them away from the forms of "teaching" that they used to practice. The article finally questions the lack of appropriate support for trainers in their appropriation of the 2009 pedagogical reengineering.